Performance Evaluation of IrishPotato (Solanum tuberosum L.) Varieties for Tuber Yield in Buno Bedele, Southwestern, Ethiopia - Abdeta, Alemayehu; Chala, Gebeyehu; Tamiru, Tolasa (Discoveries in Agriculture and Food Sciences, 2023)
In this study, adaptation trial of improved potato varieties was conducted in Buno Bedele Zone with the objective of recommending best-performing variety. Four potato varieties (Belete, Gudenie Jalanie and Horo) were evaluated for their vegetative growth performance and tuber yield under rain fed conditions. Combined analysis of data revealed that, varieties showed highly significant at (P <0.01) variations for days to maturity, number of tubers per plant, Marketable and tuber yield. The longest days to maturity (95.25 days) was recorded from Gudanie while the shortest days to maturity (87.25 days) was recorded from Horo. Besides, the tested potato varieties showed highly significant (P < 0.01) variations for the number of total tubers per hill. The highest tuber number per hill (22.37) was recorded from Belete variety where as the lowest tuber number per hill (13) was recorded from Jalanie. Variety Belete had also highest (24.24 t/ha) marketable tuber yield followed by Gudanie variety (19.14t/ha) as compared with other Varieties where as, Jalanie variety had the lowest (9.83 t/ha) marketable tuber yield. There was highly significant (p<0.01) difference in total tuber yield among the potato varieties evaluated. The highest total tuber yield (26.24 t/ha) was recorded from Belete variety followed by Gudanie variety (22.06 t/ha). On the other hand, the lowest total tuber yield (11.14 t/ha was recorded from Jalane variety which was found to be at par with Horo variety Belete and Gudenie varities were also relatively resistant to late blight diseaseas compared to other varieties. On the other hand Jalanie and Horo varieties were moderately susceptible and moderately resistant, respectively. The result of the correlation analysis also revealed that tuber number and number of tubers per plant were significantly and positively correlated with marketable and total tuber yield. Likewise marketable tuber yield was also significantly and positively correlated with total tuber yield. Belete and Gudanie were varieties that showed better performance in terms of yield and yield component as well as disease resistance. Therefore, the two varieties are recommended to be demonstrated on farmer’s field for further scaling up.